Characteristics of Paddy Gogo Stomata (Oryza sativa L.) Based on Different Altitude in Jayawijaya Regency - Anti Uni Mahanani (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
The leaves will absorb energy from sunlight and convert it into chemical energy which is stored in the form of sugar through photosynthesis. One of plants part mechanism that is controlled by sunlight is the stomata. The purpose of this study was to determine the stomata characteristics of paddy gogo leaves based on the altitude of the growing place in Jayawiaya Regency. There search was conducted in January – March 2019 in three agroecosystem zones in Jayawijaya Regency with five Paddy gogo varieties, namely the Inpago Unsoed 1 variety, Inpago Unsoed Parimas, Inpari 28, Inpago 9 and one local variety of Wamena (Moai) as comparison, which used a randomized block design method with varieties as a treatment and repeated 3 times for each agroecosystem zone. The results showed the varieties that resistant to environmental conditions in Jayawijaya Regency were Inpari 28 variety in Walelagama District (Zone1), Local of Wamena variety (Moai) in Kurulu District (Zone2) and Inpago Unsoed 1 variety in Sogokmo District (Zone3). This is because the high level of stomata density or the stomata index indicates that the plant cannot with stand water stress conditions or sub-optimall and conditions